2019
DOI: 10.1111/jai.13876
|View full text |Cite
|
Sign up to set email alerts
|

Gene characterization and expression pattern of Mx and Viperin genes in Dabry’s sturgeonAcipenser dabryanus

Abstract: Mx and Viperin are important interferon‐stimulated genes that mediate the antiviral immune response. In this study, we cloned the Mx and viperin genes from Dabry's sturgeon (Acipenser dabryanus). The Mx cDNA sequence contained an open reading frame (ORF) of 1,449 nucleotides, encoding a putative protein of 392 aa, which is significantly shorter than other animal Mx proteins. Although the similarity and identity were low between sturgeon Mx and other animal Mx proteins, sturgeon Mx contains the conserved tripar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…In other fishes, the Mx gene is also ubiquitous in different tissues, such as sea bream [25] and Japanese flounder [6]. In the present study, we found that AdMx was expressed ubiquitously in all eight examined tissues, which is similar to the expression pattern in Cirrhinus mrigala [26] and Acipenser dabryanus [27]. Moreover, AdMx showed a relative high transcript level in the brain, kidney and spleen.…”
Section: Discussionsupporting
confidence: 79%
“…In other fishes, the Mx gene is also ubiquitous in different tissues, such as sea bream [25] and Japanese flounder [6]. In the present study, we found that AdMx was expressed ubiquitously in all eight examined tissues, which is similar to the expression pattern in Cirrhinus mrigala [26] and Acipenser dabryanus [27]. Moreover, AdMx showed a relative high transcript level in the brain, kidney and spleen.…”
Section: Discussionsupporting
confidence: 79%
“…Another way relies on the catalytic activity of Viperin to generate 3′-deoxy-3′,4′-didehydro-CTP (ddhCTP), which can directly interfere with RNA synthesis and the replication of flaviviruses (33). Similar to mammal, fish viperin is considered an important antiviral gene because its expression is also induced by LPS, poly(I:C), or viruses (15,(34)(35)(36)(37)(38)(39)(40). However, little is known about the molecular mechanism underlying the antiviral effect of fish Viperin.…”
Section: Introductionmentioning
confidence: 99%
“…Immune‐related proteins such as IFNs, IFN receptors, interleukin 16/17, trim, lysozymes, antimicrobial peptides, and Toll‐like receptors (TLRs) have been characterised (Han et al., 2018; Kai et al., 2019; Youshen Li et al., 2019; Luo et al., 2018; Xu et al., 2019; Zhang, Xu, Boscari, et al., 2018; Zhang, Xu, Du, et al., 2018). The interferon‐stimulating, Mx and Viperin genes have also been reported in A. dabryanus (Zhang et al., 2019). However, there has been no report of PKR genes in A. dabryanus .…”
Section: Introductionmentioning
confidence: 89%